A COMPREHENSIVE REVIEW OF PETROLEUM-DERIVED PRODUCTS, REFINING PROCEDURES, AND CRUDE OIL FRACTIONS - Hussein Muteb Hatam; Ola Abdulhay Ali; Ayaat Khamess Ftekan (Universitas Islam Sumatera Utara, 2026)
Petroleum, known as crude oil in many countries is a non-renewable resource. It's a naturally-occurring liquid that exists beneath the Earth’s surface (lithosphere) and can potentially be extracted as an alternative fuel. Petroleum is a fossil fuel, having been made from the remains of dead plant and animal matter that was trapped under layers of sediments over millions of years. It forms in sedimentary rock where the heat and pressure is extreme. An example of a process that can demonstrate these principles is the cracking of crude oil into many useful fractions, including gasoline and its sisters in distillation known as